Criticism of the Average Allocation Mechanism and The Criticism of aoThe Criticism (Global Journal of Human-Social Science, 2012)
At the beginning of reform and opening up Chinese society for the accounting unit of the average distribution of the internal criticism of the theory and in practice reflects the very good results due to the existence of this concept to be sure the field is not correct combined with the average distribution of the old barrier development of productive forces in the angrily denounced the average allocation process people seem to be intentionally or unintentionally this criticism of the excessive expansion of the range resulting in practice at the macro level the distribution of income redistribution and ultimately was efficiency first cover look after the contrast between the different levels is too large the amount of public interest from the material strength of the different evolved into distinct groups or classes In the final analysis is due to a general criticism of the average distribution of the reasons it must be evenly distributed in the critical resources through the definition of the property of the recource scientifically for equal distribution under the cover of the income gap is too poor or in the relevant areas of the distribution range of the average distribution of the concept of recovery to achieved through the scientific development goal of building a harmonious society
Keywords: Average distribution; equally; criticism; public system